miR-205 enhances radiation sensitivity of prostate cancer cells by impairing DNA damage repair through PKCε and ZEB1 inhibition - El Bezawy, Rihan (J Exp Clin Cancer Res, 2019)
BACKGROUND: Radiotherapy is one of the main treatment options for non-metastatic prostate cancer (PCa). Although treatment technical optimization has greatly improved local tumor control, a considerable fraction of patients still experience relapse due to the development of resistance. Radioresistance is a complex and still poorly understood phenomenon involving the deregulation of a variety of signaling pathways as a consequence of several genetic and epigenetic abnormalities. In this context, cumulative evidence supports a functional role of microRNAs in affecting radioresistance, suggesting the modulation of their expression as a novel radiosensitizing approach. Here, we investigated for the first time the ability of miR-205 to enhance the radiation response of PCa models. METHODS: miR-205 reconstitution by a miRNA mimic in PCa cell lines (DU145 and PC-3) was used to elucidate miR-205 biological role. Radiation response in miRNA-reconstituted and control cells was assessed by clonogenic assay, immunofluorescence-based detection of nuclear γ-H2AX foci and comet assay. RNAi was used to silence the miRNA targets PKCε or ZEB1. In addition, target-protection experiments were carried out using a custom oligonucleotide designed to physically disrupt the pairing between the miR-205 and PKCε. For in vivo experiments, xenografts generated in SCID mice by implanting DU145 cells stably expressing miR-205 were exposed to 5-Gy single dose irradiation using an image-guided animal micro-irradiator. RESULTS: miR-205 reconstitution was able to significantly enhance the radiation response of prostate cancer cell lines and xenografts through the impairment of radiation-induced DNA damage repair, as a consequence of PKCε and ZEB1 inhibition. Indeed, phenocopy experiments based on knock-down of either PKCε or ZEB1 reproduced miR-205 radiosensitizing effect, hence confirming a functional role of both targets in the process. At the molecular level, miR-205-induced suppression of PKCε counteracted radioresistance through the impairment of EGFR nuclear translocation and the consequent DNA-PK activation. Consistently, disruption of miR-205-PKCε 3’UTR pairing almost completely abrogated the radiosensitizing effect. CONCLUSIONS: Our results uncovered the molecular and cellular mechanisms underlying the radiosensitizing effect of miR-205. These findings support the clinical interest in developing a novel therapeutic approach based on miR-205 reconstitution to increase PCa response to radiotherapy.